Perceptions of students in learning mathematics through Open and Distance Learning (ODL) / Muniroh Hamat ... [et al.] - Hamat, Muniroh; Omar, Mawardi; Ahmad, Nurhafizah; Zahari, Mohd Fahmi (Unit Penerbitan JSKM, 2021)
During times of crisis, such as the global spread of the Covid-19 epidemic, online education has seen exponential development when educators and students are forced to stay at home and resume their studies completely online. Students have no choice but to keep up with the Open and Distance Learning standards and difficulties (ODL). As online learning continues to grow, it is important to investigate students’ overall experiences in online learning environments especially in learning Mathematics. Understanding students' experiences based on their perspectives on their online classes or programs goes beyond the simple question of student satisfaction to more nuanced questions about how factors inside and outside of the classroom impact the online classroom. The purpose of this study was to investigate the experience of students in learning mathematics through Open and Distance Learning (ODL) during the COVID-19 pandemic. This study uses a methodological approach in which a questionnaire was distributed to 202 respondents on their overall views on ODL. This survey shows ODL in learning Mathematics more favor among respondents based on their learning experienced, they still hope this subject is more suitable for the classroom learning environment.